Multiple meanings of “equitable food systems”: food systems and discursive politics of change - Juskaite, Greta; Haug, Ruth (Frontiers in Sustainable Food Systems, 2023)
Calls to change or transform food systems have come to be widespread in recent years. With recognition that current food systems are not only unsustainable, but widely inequitable, these calls are increasingly articulated in terms of the need to craft ‘equitable food systems’. The purpose of this paper is to question how ‘equitable food systems’ are given meaning to in ongoing discourses that shape directions of food systems change. Finding best strategies to food systems change is a subject of intense debates, making it an inherently political affair. In this paper our strategy of knowing about these politics is analysis of discourses through which they are expressed. Through a literature review, this paper identifies four discourses driving food systems change: (a) productionism, (b) redistributionism, (c) anti-capitalism, and (d) AID: donor rescue. Drawing on insights from existent literature, the paper explores these discourses in relation to equity concerns. The analysis reveals that multiple meanings of ‘equitable food systems’ exist, hinging on varied ideas about inequity, change, and the essence of human well-being. Materializing into practical strategies to progress food systems change, multiplicity of meanings implies inevitable trade-offs when one is prioritized over the other. As such, through our analysis we contend the need for more democracy when negotiating policy directions forward. All four discourses might have some merit that could become advantageous in finding contextually appropriate pathways towards more equitable food systems. However, corporate voices and perspectives tend to be louder than those of producers, workers, and consumers, reflecting and reproducing power imbalance within policy negotiations and the global society more broadly. Bridging such power divide is thus essential to balance out food systems change discourses and allow for conductive combinations of elements from each to be created to anchor pursuits to food systems change that truly foster more equitable ways forward.